2022
DOI: 10.1556/2060.2022.00015
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections in COVID-19 patients and correlation with mortality rate. Minireview

Abstract: Purpose The goal of our review was to gather information on the most important community-acquired and hospital-acquired co-infections among coronavirus disease 2019 (COVID-19) patients, and to examine not only the effect of these co-infections on disease outcomes but also to identify the possible risk factors that predispose COVID-19 patients to co-infections. Methods Medline (PubMed) and Google Scholar were searched for relevant articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…Since the very beginning of the pandemic, co-infections of COVID-19 patients have been reported [ 18 , 19 , 35 , 36 , 37 , 38 , 39 ]. It needs to be noted that the several studies reporting superinfections have not distinctly distinguished between community-acquired and healthcare-associated infections, thus limiting the validity of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the very beginning of the pandemic, co-infections of COVID-19 patients have been reported [ 18 , 19 , 35 , 36 , 37 , 38 , 39 ]. It needs to be noted that the several studies reporting superinfections have not distinctly distinguished between community-acquired and healthcare-associated infections, thus limiting the validity of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies have also reported low rates of early infection and, rather, direct the focus to nosocomial infection [ 17 , 34 ]. Reported rates of secondary bacterial infections in critically ill ICU patients with COVID-19 have ranged from 8.1% to 42.8% [ 13 , 17 , 18 , 34 , 35 , 36 , 37 , 38 , 39 ]. There is also a wide range of reported infection rates with respect to secondary fungal infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the structure of secondary lymphoid organs is essential for immune defense against microbes, their breakdown during an ongoing virus infection may temporarily reduce immune competence toward other infections ( 72 ). Second, it has been suggested that COVID-19 associated lymphopenia may contribute to a higher rate of bacterial co-infections ( 73 , 74 ). Finally, signs of T cell exhaustion, such as PD-L1 overexpression, are observed in some COVID-19 patients, and this may further limit the immune competence of COVID-19 patients toward other pathogens ( 75 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, signs of T cell exhaustion, such as PD-L1 overexpression, are observed in some COVID-19 patients, and this may further limit the immune competence of COVID-19 patients toward other pathogens ( 75 78 ). Since multiple risk factors for bacterial co-infections have been described in COVID-19 patients, it is likely that multiple immunological mechanisms are at play and determine the individual risk ( 74 ).…”
Section: Discussionmentioning
confidence: 99%